Sustaining teaching during a crisis - Marcia D Dixson; Julie Saam (Journal of the Scholarship of Teaching and Learning, 2024)
Given the increasing demands on faculty in higher education, it is imperative that we better understand how to support faculty across their careers and in all areas of faculty life.  This study looks specifically at what it takes to support teaching during the added stress of a global crisis.  An exploratory survey of 66 faculty at midwestern campuses indicates that Satisfaction with teaching as a career, Passion for teaching, and Quality of teaching require different things.  Specifically, Satisfaction with teaching requires motivation. Passion for teaching needs time. Quality of teaching, on the other hand, requires motivation, support, and time.  What these concepts consist of and how we might use this information to support our own and our colleagues’ teaching is discussed.